Farmer's regulation by Muhammad Ali 1830 from legal and social perspectives - Moustafa, Enas (AUC Knowledge Fountain, 2017)
The FR played an important role in the Egyptian rural life. It shaped the relation between the farmers and the state. It mainly helped the state to impose tax, collect it and make use of it. The social and anthropological changes the FR caused helped in the formation of modern Egypt. However the FR penalties were characterised with severity, as the punishment was not compatible with the offence being committed. This cruelness made the Egyptian peasant tries to escape the land and always have a hostile relation with the system. The thesis is to examine the various FR articles, its different parts and implications. It would be crucial to show that the penalties were not sharia based although the legislator tried to indicate otherwise. The cases examined showed that the penalties were mainly to cater for the state’s benefit rather than the farmers’ one. However, the legislative Egyptian body worked to make the FR as a method of standardization.